2011
DOI: 10.1289/ehp.1002927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Improved Patsari Biomass Stove on Urinary Polycyclic Aromatic Hydrocarbon Biomarkers and Carbon Monoxide Exposures in Rural Mexican Women

Abstract: Background: Cooking with biomass fuels on open fires results in exposure to health-damaging pollutants such as carbon monoxide (CO), polycyclic aromatic hydrocarbons (PAHs), and particulate matter.Objective: We compared CO exposures and urinary PAH biomarkers pre- and postintervention with an improved biomass stove, the Patsari stove.Methods: In a subsample of 63 women participating in a randomized controlled trial in central Mexico, we measured personal CO exposure for 8 hr during the day using continuous mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 32 publications
10
38
1
Order By: Relevance
“…A few studies have characterized the risk of exposure to PAHs due to residential combustion of different biomass fuels by measuring PAH levels at breathing zone height in cooking environments (Bhargava et al, 2004;Hamada et al, 1991;Oanh and Dungs, 1999;Pandit et al, 2001) and under experimental conditions (Oanh et al, 2002) and report that various PAHs are elevated during the combustion of wood, kerosene, cow dung and coal briquette. Results of biomarker studies have shown that people exposed to smoke from biomass combustion have elevated levels of hydroxy-substituted PAHs in urine (Cavanagh et al, 2007;Kato et al, 2004;Li et al, 2011;Riojas-Rodriguez et al, 2011;Viau et al, 2000), and receive a significant PAH exposure from biomass smoke RiojasRodriguez et al, 2011). Reductions in urinary two-to four-ring OH-PAHs after the installation of improved woodstoves ranged from 19% to 52% in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru , and from 20% to 42% in women participating in a similar program in the state of Michoacan in Mexico (Riojas-Rodriguez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have characterized the risk of exposure to PAHs due to residential combustion of different biomass fuels by measuring PAH levels at breathing zone height in cooking environments (Bhargava et al, 2004;Hamada et al, 1991;Oanh and Dungs, 1999;Pandit et al, 2001) and under experimental conditions (Oanh et al, 2002) and report that various PAHs are elevated during the combustion of wood, kerosene, cow dung and coal briquette. Results of biomarker studies have shown that people exposed to smoke from biomass combustion have elevated levels of hydroxy-substituted PAHs in urine (Cavanagh et al, 2007;Kato et al, 2004;Li et al, 2011;Riojas-Rodriguez et al, 2011;Viau et al, 2000), and receive a significant PAH exposure from biomass smoke RiojasRodriguez et al, 2011). Reductions in urinary two-to four-ring OH-PAHs after the installation of improved woodstoves ranged from 19% to 52% in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru , and from 20% to 42% in women participating in a similar program in the state of Michoacan in Mexico (Riojas-Rodriguez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Results of biomarker studies have shown that people exposed to smoke from biomass combustion have elevated levels of hydroxy-substituted PAHs in urine (Cavanagh et al, 2007;Kato et al, 2004;Li et al, 2011;Riojas-Rodriguez et al, 2011;Viau et al, 2000), and receive a significant PAH exposure from biomass smoke RiojasRodriguez et al, 2011). Reductions in urinary two-to four-ring OH-PAHs after the installation of improved woodstoves ranged from 19% to 52% in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru , and from 20% to 42% in women participating in a similar program in the state of Michoacan in Mexico (Riojas-Rodriguez et al, 2011). In this study, we investigated exposure to PAHs among pregnant women who use uniquely one or combinations of fuel types for cooking and heating.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A number of studies have used urinary OH-PAHs as the woodsmoke exposure biomarker to investigate stove emissions and evaluate the effectiveness of stove intervention efforts. 2831 …”
Section: Introductionmentioning
confidence: 99%
“…The half-life of urinary 1-hydroxypyrene (1-OHP) excretion ranges from 4 to 35 h 3. Information on the half-lives of the other OH-PAHs is scarce; however, because similar metabolites are formed under similar biological pathways, other OH-PAHs are assumed to have similar half-lives 4. Due to the short half-lives of PAH, information provided by biomonitoring of urinary OH-PAH is limited to recent exposure 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the half-lives of the other OH-PAHs is scarce; however, because similar metabolites are formed under similar biological pathways, other OH-PAHs are assumed to have similar half-lives 4. Due to the short half-lives of PAH, information provided by biomonitoring of urinary OH-PAH is limited to recent exposure 3 4. Recent studies, including those from our lab,5 6 found that occupational exposure to PAH is associated with decreased cardiac autonomic function, as assessed by heart rate variability (HRV), which is one of the major mechanistic pathways for adverse cardiac events.…”
Section: Introductionmentioning
confidence: 99%